The Manasseh hill country survey. - Zertal, Adam. (Culture and History of the Ancient Near East, 2016)
The volume presents the results of a detailed survey of north-western Samaria in Israel/Palestine. It is the third volume of the Manasseh Hill Country Survey publications. This project, in progress from 1978 and covering 2500 sq. km, is a thorough mapping of the archaeological-historical area between the River Jordan and the Sharon Plain and between Nahal 'Iron and the Dead Sea. The survey is a valuable tool for scholars of the Bible, Archaeology, Near Eastern history and other aspects of the Holy Land. This volume describes the area between Nahal 'Iron (Wadi 'Ara) in the north and Nahal Shechem (Wadi She'ir) in the south. It is a fully revised and updated version of the Hebrew publication of 2000.